KUALITAS VISUM ET REPERTUM PERLUKAAN DI RUMAH SAKIT UMUM DAERAH SIAK PERIODE 1 JANUARI 2009-31 DESEMBER 2013 - Intan Rosaline Simangunsong; Dedi Afandi; Laode Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe most frequent Visum et repertum (VeR) requested by investigators is VeR of injury. This study was aimed to understand the quality of VeR of injury in Siak General Hospital during 1st January 2009-31st December 2013. The research was an observational study using descriptive retrospective design. This study used Herkutanto’s scoring method towards 13 VeR substances. Samples of this study were all data of VeR of injury. It had been gotten 78 VeR reports in Siak General Hospital during 1st January 2009-31st December 2013. Injury survivors most cases are in the age group 22-40 years old as many as 39 victims (50%). The overview of the living victims were most frequent male was 52 victims (66,7%) and the most frequent violence that were experienced by the victims were blunt violence was 72 VeR (92,3%)with the highest age group 22-40 years old. About 75,8% showed good quality in preliminary unit of VeR, 48% showed poor quality in reporting unit and about 53% showed medium quality in inference unit. It can be concluded that quality of VeR reports in Siak General Hospital during 1st January 2009-31st December 2013 was 52,97% which was mean it was medium quality.Keywords: Visum et Repertum, injury, quality of VeR of injury